Philosophy and the Mirror of Nature : Thirtieth-Anniversary Edition - Rorty, Richard (Book collections on Project MUSE., 2009)
30 years ago Richard Rorty argued that philosophers had developed an unhealthy obsession with the notion of representation: comparing the mind to a mirror that reflects reality. The book now stands as a classic of 20th-century philosophy.